Early detection of non‐tuberculous mycobacteria in children with cystic fibrosis using induced sputum at annual review. Issue 3 (18th December 2018) - Ahmed, Molla I.; Kulkarni, Hemant; Shajpal, Sarita; Patel, Deepa; Patel, Prakash; Claydon, Alison; Modha, Deborah E.; Gaillard, Erol A.
Abstract: Aim: Non‐tuberculous mycobacteria (NTM) have emerged as an important pathogen in cystic fibrosis (CF). Early detection and treatment of NTM can preserve lung function and maintain good lung health. Many children with CF are not regular sputum producers and cough swabs cannot routinely be used to diagnose NTM. We aimed to test the hypothesis that performing sputum induction at routine annual review results in earlier identification of NTM in non‐sputum producing children with CF. Method: We conducted a 5‐year prospective observational cohort study involving children with CF aged 5‐17 years who had sputum induction with hypertonic saline for microbiological surveillance including NTM at their annual review. Results: Forty‐two children (19 males, mean age 11.4 years ± 3.6, mean FEV1 % predicted 94.7 ± 20.6) participated in the study. Forty‐one induced sputum samples from 29 children yielded bacterial pathogens. Six samples from six children (14% of the cohort) yielded NTM never previously isolated from the patient. We also detected three isolates of Pseudomonas aeruginosa and one isolate each of Burkholderia cepacia complex and Meticillin resistant Staphylococcus aureus (MRSA), all of which were first time isolates. Conclusion: We conclude that annual induced sputum for microbiological surveillance is useful for early detection of NTM and other important respiratory pathogens, particularly in non‐expectorating children. This may lead to earlier identification and help inform initiation of eradication treatment in children with NTM. Children can also be cohorted earlier, before they potentially infect other children in the clinic.